2017
DOI: 10.1038/gim.2016.95
|View full text |Cite|
|
Sign up to set email alerts
|

Candidate-gene criteria for clinical reporting: diagnostic exome sequencing identifies altered candidate genes among 8% of patients with undiagnosed diseases

Abstract: Purpose:Diagnostic exome sequencing (DES) is now a commonly ordered test for individuals with undiagnosed genetic disorders. In addition to providing a diagnosis for characterized diseases, exome sequencing has the capacity to uncover novel candidate genes for disease.Methods:Family-based DES included analysis of both characterized and novel genetic etiologies. To evaluate candidate genes for disease in the clinical setting, we developed a systematic, rule-based classification schema.Results:Testing identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 40 publications
0
58
0
Order By: Relevance
“…Genomic DNA extraction, exome library preparation, sequencing, bioinformatics, and data analyses were performed as previously described. 24,25 Identified candidate variants were confirmed via Sanger sequencing.…”
Section: Genetic Analysismentioning
confidence: 99%
“…Genomic DNA extraction, exome library preparation, sequencing, bioinformatics, and data analyses were performed as previously described. 24,25 Identified candidate variants were confirmed via Sanger sequencing.…”
Section: Genetic Analysismentioning
confidence: 99%
“…For individual 10, parent-proband trio WES was performed at Ambry Genetics using the IDT xGen Exome Research Panel and analyzed as previously described. 36,37 On average, $96.6% of the target bases were covered at >203 for the trio. The de novo frameshift alteration identified in this patient by WES was confirmed by Sanger sequencing and interpreted as a (suspected) candidate gene finding.…”
Section: Microarray and Molecular Analysesmentioning
confidence: 99%
“…The de novo frameshift alteration identified in this patient by WES was confirmed by Sanger sequencing and interpreted as a (suspected) candidate gene finding. 37 …”
Section: Microarray and Molecular Analysesmentioning
confidence: 99%
“…The remaining negative reclassification report was due to new literature disputing the pathogenicity of alterations in the identified gene ( SRI ; MIM# 182520). Within the first 500 cases, we previously reported that in cases in which a candidate genetic etiology was initially reported, 51.9% had subsequent corroborating evidence in the literature [Farwell Hagman et al., ]. Of the current cohort of 80 candidate genetic etiology reports, 28 subsequently were issued a reclassification report, that is, 35% of all candidate genetic etiology reports were subsequently reclassified to positive/likely positive in characterized genes.…”
Section: Methodsmentioning
confidence: 94%